2005
DOI: 10.1007/bf02287328
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of a scale measuring parent satisfaction with staff interactions

Abstract: This study tested the psychometric properties of the Parent Satisfaction Scale (PSS), a new scale measuring parents' satisfaction with their child's mental health services, primarily focusing on staff's interpersonal interactions. Data were collected by postal surveys 5 to 10 months after a child's admission to 1 of 5 mental health treatment programs. Completed surveys were received from parents of 120 of a potential 232 children (52% response rate). Internal consistency reliability of the PSS was strong (alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…When it comes to user satisfaction, it has already been shown that the essential aspects are: patient-professional interactions, physical environment and internal management processes 17,18,22,23 . However, services with some different characteristics (home care, out-of-hours, psychiatric and pediatric services, and more multidisciplinary complex services) usually utilized other specific elements, such as phone contact or clear information to the caregiver 18,24,25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When it comes to user satisfaction, it has already been shown that the essential aspects are: patient-professional interactions, physical environment and internal management processes 17,18,22,23 . However, services with some different characteristics (home care, out-of-hours, psychiatric and pediatric services, and more multidisciplinary complex services) usually utilized other specific elements, such as phone contact or clear information to the caregiver 18,24,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Only three studies showed a unidimensional structure for the tested instrument 22,32,48 . However, there is not a clear pattern of what the essential dimensions (factors) that must be included in a satisfaction measurement are.…”
Section: Satisfaction Constructmentioning
confidence: 99%
See 2 more Smart Citations
“…Each therapeutic community, although formed by disparate individuals, develops a common 'matrix' of relationships and communications as a result of its history and circumstances, and a specific 'culture' 8 that supersedes the individuals and expresses a group view over different issues. This consensus, along with the essential negotiation to reach it, goes beyond aggregates or 'averages' obtained from approaching individual service users who may not adequately represent their community 9 and ensures the representativeness of its findings. This study describes a methodological approach to purposefully processing service users' views in order to develop and pilot a structured tool (Service User Informed Tool for Staff Selection, SUITSS) for gathering the views of the community of service users on NHS staff applicants during the process of recruitment.…”
Section: Discussionmentioning
confidence: 99%